O rozmieszczeniu władzy we współczesnych organizacjach - Hopej, Marian; Kamiński, Robert (A power arrangement in modern organizations, 2005)
In the article was shown the image of modem, high flexible structural solutions, which could be found in the literature. The thesis was the practice of management enlarges the role which centralized management systems and structures do play. The thesis was verified at the example of LGS Group.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 491-497